2018
DOI: 10.1113/jp275611
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exercise impairs nitric oxide pathway in rabbit carotid and femoral arteries

Abstract: The present study aimed to evaluate the effects of chronic exercise on vasodilator response in two different arteries. Rings of carotid and femoral arteries from control and trained rabbits were suspended in organ baths for isometric recording of tension. Endothelial nitric oxide synthase (eNOS), Cu/Zn and Mn-superoxide dismutase (SOD), and large conductance calcium activated potassium (BKCa) channel protein expression were measured by western blotting. In the carotid artery, training reduced the relaxation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
5
0
1
Order By: Relevance
“…Marchio et al investigated the effect of long-term training on femoral arteries in male New Zealand white rabbits. In accordance with our results, during the relaxation test with Ach, trained and sedentary groups did not demonstrate differences [ 26 ]. Male Sprague Dawley rats also showed no alterations in response to Ach in a previous study [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Marchio et al investigated the effect of long-term training on femoral arteries in male New Zealand white rabbits. In accordance with our results, during the relaxation test with Ach, trained and sedentary groups did not demonstrate differences [ 26 ]. Male Sprague Dawley rats also showed no alterations in response to Ach in a previous study [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The role of exercise in CAS remains controversial. A 6-year clinical trial showed that aerobic physical activity did not slow the progression of CAS ( 27 ) and might contribute to carotid endothelial injury ( 28 ). However, some studies have shown that lack of exercise is a risk factor for CAS ( 11 , 26 ), and aerobic exercise could help combat carotid intima-media thickening in obese patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the protocols for exercise training in rabbits ( Table 2 ) begin with an adaptation phase for the animal, called the familiarization period. This period varies from 3 days [ 34 ], 4 days [ 35 , 36 ], or 1 week [ 31 , 32 , 33 , 37 , 38 ], to several weeks [ 24 , 29 , 39 , 40 , 41 ]. These adaptation periods should be constantly monitored (observation and accompaniment) to avoid the animals running inappropriately or stopping during the execution of the training protocol [ 35 ].…”
Section: Exercise Training Protocols In Rabbitsmentioning
confidence: 99%
“…Each session is divided into 6 exercise intervals. The animals run for 4 min at a speed, depending on the study, of 0.33 m/s [ 21 , 36 ] or 0.5 m/s [ 35 ], separated by a 1 min rest between each run.…”
Section: Exercise Training Protocols In Rabbitsmentioning
confidence: 99%
See 1 more Smart Citation